The Efficiency of German Universities Some Evidence from Non-Parametric and Parametric Methods - Gerhard Kempkes; Carsten Pohl (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2006)
Due to tight public budget constraints, the efficiency of publicly financed universities in Germany is receiving increasing attention in the academic as well as in the public discourse. Against this background we analyze the efficiency of 72 public German universities for the years 1998 to 2003, applying data envelopment and stochastic frontier analysis. Contrary to earlier studies we account for the faculty composition of universities, which proves to be an essential element in the efficiency of higher education. Our main finding is that East German universities have performed better in total factor productivity change compared to those in West Germany. However, when looking at mean efficiency scores over the sample period, West German universities still appear at the top end of relative efficiency outcomes.
Keywords: M11; I21; 330; universities; efficiency; data envelopment analysis; stochastic frontier analysis